Analysis of writing in personality disorders in prison population - Muñoz-López, Lucas; Fernández-García-Valdecasas, Borja; López-Rodríguez, Slava; Sánchez-Barrera, María Blanca (Frontiers in Psychiatry, 2024)
Abstract Writing involves the activation of different processing modes than reading comprehension, and therefore the level of activation varies depending on the moment and the task. Objectives to analyze the profiles in terms of the proposed coding from the PROESC in terms of personality disorders [Antisocial Personality Disorder (ASPD) with drugs possession and consumption crimes (DPCC) and Obsessive-Compulsive Personality Disorder (OCPD)] with gender violence crimes (GVC) in the prisoners. Design The sample was composed of 194 men. The participants were divided into two groups. Group 1 (ASPD; DPCC) consisted of 81 men, and Group 2 (OCPD; GVC) consisted of 113 men. Main outcome measures They completed the Demographic, Offense, and Behavioral Interview in Institutions, the International Personality Disorders Examination (IPDE), and Writing Processes Evaluation Battery (PROESC). Results Group 2 made more mistake than Group 1 in narratives tasks. Conclusion Participants know phoneme-grapheme correspondence rules, language disturbances of a reiterative and persistent nature may appear in those who show compulsive behavior.